STRATEGI PEMASARAN DALAM KEGIATAN PENJUALAN PROPERTI UNIT RUMAH CIRACAS GREEN VIEW PADA PT MAXIRECON - Auliya, Delfi Nur; Muis, Indra (JURNAL MAHASISWA BINA INSANI, 2023)
The purpose of the discussion is to analyze the marketing strategy carried out, find out the obstacles faced and how the solution in solving it. Data analysis using descriptive qualitative methods. Data collection using interview, observation, and documentation techniques. The conclusion of this study shows that Ciracas Green View has applied the concept of a good marketing strategy using the STP and 4P methods related to each other to marketing. CGV has a market segment, namely, the target market based on the area of Jakarta City, employment, income and lifestyle of consumers. CGV has a clear market position and can be compared with similar housing. CGV's marketing mix provides Exclusive and modern residential home products at affordable prices, located in the city of Jakarta which is very strategic in reaching public facilities and infrastructure, and promotions carried out using social media and collaborating with property agents in marketing activities. In this study, it can be concluded that the lack of utilization of TikTok social media in carrying out promotional activities. The proposal that can be given is to create a separate TikTok account by presenting interesting content to users that can be used as promotional media to help businesses be better known by many people.